The Emergence and Development Process of Scientific Exegesis - Taghiyev, Kovsar (Scholarya Demo Journal of Ruby, 2018)
The Holy Qur’an that sent down to call people for true faith and true morality, brings forward the natural harmony as the evidence to convince them to its principles. Quranic verses and its interpretations that have been made from early Islamic period to the present day, play crucial role in Tafsir. The basic characteristics of the scientific exegesis are to extract evidences for various domains of science from the Qur’an through linking verses to natural sciences and consider the Holy Qur’an as the source of all branches of science. It is possible to encounter the precedents of scientific exegesis in the early sources of Tafsir. However, the theoretical basis of this type of exegesis was founded by Abu Hamid al-Ghazali. Scientific interpretation, which shows itself in practice with the help of Fakhraddin Razi’s works, experienced the period of stagnation until the last century. In the 19th and 20th centuries, when positivist thinking overrode all religions, scientific exegesis was revived, and a plenty of literature appeared related to this field. This article examines the historical periods of development of the concept of scientific interpretation, suggests that this concept is apologetic in nature, and also notes that the scientific interpretation of the Qur’an, faced with numerous critical comments from a methodological point of view, is experiencing serious difficulties in recent times.